If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 7) + -43 = 4 + -35 Reorder the terms: -6(7 + x) + -43 = 4 + -35 (7 * -6 + x * -6) + -43 = 4 + -35 (-42 + -6x) + -43 = 4 + -35 Reorder the terms: -42 + -43 + -6x = 4 + -35 Combine like terms: -42 + -43 = -85 -85 + -6x = 4 + -35 Combine like terms: 4 + -35 = -31 -85 + -6x = -31 Solving -85 + -6x = -31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '85' to each side of the equation. -85 + 85 + -6x = -31 + 85 Combine like terms: -85 + 85 = 0 0 + -6x = -31 + 85 -6x = -31 + 85 Combine like terms: -31 + 85 = 54 -6x = 54 Divide each side by '-6'. x = -9 Simplifying x = -9
| x/-9=-5-(-7) | | d=65*5 | | 9x+17-8x=-2-10 | | 13x+8y=1163 | | D=65mph*5hours | | 78y=11(7y+40) | | 8-8=10x+8x | | (3-z)(5z-7)=0 | | 7y-x=14 | | 19-16=x/-7 | | 5a^2b^2c-15abc^2=0 | | f(x)=100x-11x^2+8 | | -3x=4-(-5) | | (2x^2-3)(x+4)=21(x-2) | | A=12m*6m | | (2w-5)(2w+6v+1)= | | 4x^2=20x-17 | | 10x^3+45x^2+50x=0 | | 14x^2=22 | | 14x^2-22=0 | | x^2-20x+0= | | 14x=22/x | | 2x+5y=4 | | 14x-22/7 | | 3(2x-7)=5x+15 | | -11a+5a=7 | | y=40/9x | | 7=-11a+5a | | 6x/5-x=10 | | 3-x=12(x-1) | | 12-6=18 | | -2sin(x)+2cos(2x)=0 |